Strict Liability in the Field of Taxation: Comparison between United States and United Kingdom - Leo B. Barus; Ryan S. Alam (Criminal Law and Policy Review, 2022)
The prevalence of tax avoidance and tax evasion in the form of tax law loophole abuse, both internationally and nationally, needs to be answered with studies that discuss strict liability arrangements. Based on a comparative study between the United States and the United Kingdom, it is concluded that the handling of tax avoidance and tax evasion in order to save state revenue from the tax sector is adequately carried out by explicitly regulating strict liability in Indonesia. It is hoped that this liability arrangement will provide general benefits to the state in the form of a solution to the problem of rampant violations in the areas of social welfare which carry very high risks and/or the prevalence of certain behaviors in society which in practice must prioritize strict liability rules.